TROPICAL DAYLIGHT AVAILABILITY AND SKY TYPOLOGIES FOR DAYLIGHTING EVALUATION AND DESIGN - Moses Iorakaa Ayoosu; Yaik-Wah Lim; Pau Chung Leng; Thomas Terna Aule; Abdurraheem Bello Abdurrahman; Sa'adatu Aminu, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Daylighting in buildings is a critical functional requirement in the tropical climate. It has numerous benefits, whereas poor implementation is bound to create high energy consumption and user's discomfort, unlike in the temperate region. Daylight data for design is fundamental toward achieving optimal daylighting due to variations for different locations. Like most regions in the tropics, Nigeria has limited data in this regard. Therefore, this study investigated the availability of daylight and skies using daylight modelling methods. The global illuminance and irradiance data were input to model the outdoor daylight and sky types. The modelled, measured, and RadianceIES outdoor illuminance data were comparatively analysed relative to the design time and date. The results show that the sky is predominantly intermediate. More so, the monthly mean outdoor illumination varies from 47 to 67 klux at noon and as low as 9 klux during the morning and late afternoon. The study concluded that the mean outdoor illuminance for design is 30.7klux, 60.0klux, and 46.0klux at 0900, 1200, and1500 hours, respectively. In architecture, the use and applications of these data are to improve thermal, visual comfort, low-energy and task illuminance design in buildings, thus resulting in enhanced performance, cost savings, and user satisfaction.